COMPETENCY, ENTREPRENEUR CHARACTERISTIC AND BUSINESS PERFORMANCE: STUDY OF THE PEMPEK BUSINESS IN PALEMBANG - Soejono, Fransiska; Mendari, Anastasia Sri; Rinamurti, Micheline (Journal of Indonesian Economy and Business, 2015)
The purpose of this study was to examine empirically the effects of entrepreneurial compe-tencies and characteristics on business performance. Previous studies found that competencies and entrepreneurial characteristics significantly influenced business performance. A quantita-tive method was used and 122 respondents were involved as the sample in this study, who were pempek business owners in Palembang, South Sumatra. The results indicated an effect from entrepreneurial competencies on business performance. It was also found that the entrepre-neursâ characteristics (ownersâ ages) significantly affected the businessesâ performance. This implication requires some sort of course or program for the entrepreneurs to improve their competence to direct the owners to gain better business performance. The growing age of the business owners requires equal insights to ensure age does not stop the owners from improving their businessâ performance.Keywords: competency, characteristics, performance, age, entrepreneur